Gas Chromatographic Mass Analysis and Further Pharmacological Actions of Cymbopogon proximus Essential Oil - Al-Taweel, A. M.; Fawzy, G. A.; Perveen, S.; El Tahir, K. E. H. (Drug Research, 2013)
The present study reports Gas chromatographic mass analysis (GC-MS) as well as important biological activities of Cymbopogon proximus essential oil. The chemical composition of the essential oil of Cymbopogon proximus was investigated by GC-MS. Furthermore, the effects of Cymbopogon proximus essential oil on the cardiac parasympathetic ganglia in rats, the intra-tracheal pressure in guinea-pigs and on carrageenan-induced inflammation in the rat̓s paw, were studied. The GC-MS study led to the identification of 22 components with Piperitone representing (73.81%), Elemol (9.32%), alpha-Eudesmol (5.21%) and alpha-Terpineol (3.01%) of the oil̓s composition. The percentage protective effect of the oil on the vagus-induced bradycardia in rats was 90.1±3.1%, which represents a significant protection. As for the effect of Cymbopogon oil on bronchoconstrictors-induced increase in intra-tracheal pressure in guinea-pigs, the oil antagonized the actions of 5-HT and histamine by 80±3.7 and 93±8.3%, respectively. Pharmacological investigations using Cymbopogon oil revealed its inherent ability to possess a bronchodilator activity mediated via blockade of both histamine and serotonin receptors. It possessed a significant ganglionic blocking action and a limited anti-inflammatory activity that seemed to involve blockade of histamine and serotonin receptors in the rats’ paws.
Keywords: bronchodilator activity; cymbopogon proximus; essential oil